(untitled) (Historia, 2021)
Birds of a feather: totalitarian ideologies in the twentieth century For various reasons it has long been taboo to name communism and national socialism in the same breath or to compare them. Since the publication of Stéphane Courtois' sensational book about the crimes of communism in 1997 this is, however, being done more and more. In this article the comparison is made by looking at the systemic resemblances and differences, the natural affinity that leaders like Hitler and Mussolini on the one hand and Stalin on the other displayed towards each other, and the easy way in which they exchanged their enmity for cooperation. the conclusion is that there were indeed differences in content, but that the way in which they manifested themselves in practice, the mentality behind the ideologies, showed great similarities.